HIGHER EDUCATION IN INDIA: CHALLENGES AND OPPORTUNITIES - Pinki; Aryan; Neha (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The higher education system of any country plays a very important role. Without this, the people of the country cannot achieve anything. The level of education in a country like India is very old. Here the teacher was given the status of God. In this paper, we will know what is the status of higher education in India. How and when which policy came? We will describe all this in India, what is the history of higher education. What is the problem in higher education inside India? How can we overcome these? We will tell all this in this paper. We have reviewed more than ten papers. We have made this article after seeing them all. This we will know how higher education developed in India. What committee did what? When and how all this happened, we will discuss in this article. We will also know about the issue of higher education, and what is what. We will know about all these things in detail.